(untitled) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The purpose of the study was to examine the effect of Perceived Usefulness, Perceived Ease Of Use, and Perceived Security on Purchase Interest in Shopee through Trust as a Mediating Variable in Klaten Regency. The population used in the study was the people of Klaten Regency. The technique used in sampling in research is non probability sampling with purposive sampling method. In the study obtained a sample of 200 respondents. Data was collected through direct distribution of the hard file questionnaire to respondents. Data analysis uses linear regression and Sobel Test using AMOS (Analysis Moment Of Structural). The results in this study indicate that Perceived Usefulness, Perceived Ease Of Use, and Perceived Security have a positive and significant effect on Trust. Perceived Usefulness, Perceived Ease Of Use, and Perceived Security have a positive and significant effect on Purchase Intention. Trust has a positive and significant effect on Purchase Intention. Trust has a positive and significant effect on mediating the relationship between Perceived Usefulness and purchase intention, Trust has a positive and significant effect on mediating the relationship between Perceived Ease Of Use and purchase intention, Trust has a positive and significant effect on mediating the relationship between Perceived Security and purchase intention.